Adaptive Link Aware on-demand Multicast Routing Scheme in MANET - Ruban Chakravarthy; G. Ranganathan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The main objective of this paper is to propose a new multicast routing scheme to adopt with the dynamic topology of MANET at the same time to provide high multicast efficiency and packet delivery ratio. The proposed scheme is named as Link Aware on Demand Multicast Routing (LAOMR) scheme. In this scheme, initially the source node forms the multicast group by announcing itself as a multicast source agent to all the nodes in the network. The nodes which are eager to join in the group are sending the join request to the source node. Then the source node finds the route to reach the multicast group through some intermediate nodes. The intermediate nodes are not interested to hear the multicast message but they are act as the routers to forward the packets to the multicast group. The intermediate nodes are chosen based on the link residual life (LRL) of the nodes. The node which has the highest LRL and closer to the multicast group is selected as the forwarder node. So, the proposed scheme reduces the link failure in the multicast route and increases the multicast efficiency, throughput. The performance is evaluated by using the simulation results obtained from NS2 Simulator.